Legal methods of combating the illegal labor market - Остапенко, Леонід; Ostapenko, Leonid (Видавництво Львівської політехніки, 2022)
У статті проаналізовано існуючі підходи до визначення шляхів та методів аналізу юридичних методів боротьби з нелегальним ринком праці. У статті розкрито аспекти впливу нелегального ринку праці на український національний ринок праці. Виділяються ключові точки, у яких відбувається взаємодія ринкових процесів та проводиться аналіз можливих трансформацій. Водночас звернена увага на напрями проведення державної політики України у сфері зайнятості і працевлаштування населення на гарантії захисту прав, свобод і законних інтересів як працівника, так і роботодавця. Розглянуто наукові підходи щодо тлумачення терміну “ринок праці”, який має різне за змістом пояснення, що залежить від об’єкта і предмета дослідження. Відповідно до теми дослідження виділено групу методів економічного і правового змісту, серед яких: проведення реформ податкової (фіскальної) системи, що вплинуло на розгляд сутності і змісту так званих “тіньових доходів”, які мають тісний зв’язок з нелегальним ринком праці та підпільним виробництвом; акцентована увага на необхідності подальшого реформування існуючої на сьогодні системи наглядових і контролюючих органів у сфері виробництва за винятком безпеки та охорони праці.

The article analyzes the existing approaches to determining the ways and methods of analyzing legal methods of combating the illegal labor market. The article reveals aspects of the impact of the illegal labor market on the Ukrainian national labor market. There are key points at which the interaction of market processes takes place and the analysis of possible transformations is carried out. At the same time, attention is paid to the directions of Ukraine's state policy in the field of employment and employment of the population on guarantees of protection of the rights, freedoms and legitimate interests of both the employee and the employer. Scientific approaches to the interpretation of the term “labour market”, which has a different explanation in content, depending on the object and subject of research, are considered. Scientific approaches to the interpretation of the term “labour market”, which has a different explanation in content, depending on the object and subject of research, are considered. In accordance with the topic of the study, a group of methods of economic and legal content was identified, including: carrying out reforms of the tax (fiscal) system, which influenced the consideration of the essence and content of the so-called "shadow incomes", which have a close connection with both the illegal labor market and underground production; attention is focused on the need for further reform of the current system of supervisory and controlling bodies in the field of production, with the exception of safety and labor protection.
Про юридичні методи боротьби з нелегальним ринком праці
Keywords: тіньовий ринок праці; тіньові доходи; ухилення від податків; юридичні методи боротьби; національний ринок праці; міграція; трансформація національного ринку праці; shadow labor market; shadow income; tax evasion; legal methods of struggle; national labor market; migration; transformation of the national labor market; 349.2 (477)